2003
DOI: 10.1143/jjap.42.5315
|View full text |Cite
|
Sign up to set email alerts
|

Radical Species Formed by the Catalytic Decomposition of NH3on Heated W Surfaces

Abstract: The catalytic decomposition processes of NH 3 on heated W surfaces were examined by employing laser spectroscopic techniques. H atoms and NH 2 radicals were identified as primary decomposition products on the catalyzer surfaces. The effective enthalpies for the production of these species were both determined to be 150 kJ/mol. NH radicals were also identified, but the production of this species is ascribed to secondary processes. N atoms are minor products in both the primary and secondary processes. The absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 41 publications
8
71
0
Order By: Relevance
“…The decrease of the SiH 3 + signal intensity with temperature has also been demonstrated by Tange et al 27 Umemoto et al 29 has shown that the NH 2 radical intensity grows with filament temperature, and this is confirmed in our previous work with 50% NH 3 in the HWCVD reactor. An important question to be addressed in studying the gas-phase reaction chemistry of SiH 4 -NH 3 mixtures in HWCVD is whether or not there is any cross-talk between SiH 4 and NH 3 molecules and their respective filament decomposition products during the formation of disilane and trisilane.…”
Section: 23supporting
confidence: 89%
See 1 more Smart Citation
“…The decrease of the SiH 3 + signal intensity with temperature has also been demonstrated by Tange et al 27 Umemoto et al 29 has shown that the NH 2 radical intensity grows with filament temperature, and this is confirmed in our previous work with 50% NH 3 in the HWCVD reactor. An important question to be addressed in studying the gas-phase reaction chemistry of SiH 4 -NH 3 mixtures in HWCVD is whether or not there is any cross-talk between SiH 4 and NH 3 molecules and their respective filament decomposition products during the formation of disilane and trisilane.…”
Section: 23supporting
confidence: 89%
“…Our examination of the reaction chemistry of NH 3 in the HWCVD process has found that the major gas-phase products correspond to hydrogen and nitrogen. 14,15 The deposition chemistry of ammonia in the HWCVD process has been well characterized by Umemoto et al 29 They have identified H and NH 2 radicals as the primary decomposition products of NH 3 on the hot W filaments. Signals from H 2 and N 2 were also detected using mass spectrometry.…”
Section: 23mentioning
confidence: 99%
“…In this technique, radical species are produced from material gases on heated metal surfaces without co-producing ionic or metastable excited species. In order to make clear the decomposition and ejection mechanisms, many studies have been carried out to identify the radical species produced [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Although it has been rather difficult to produce oxidizing radicals, we have recently shown that atomic oxygen can be produced efficiently by the catalytic decomposition of O 2 , NO, N 2 O, and NO 2 on a heated Ir filament [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Laser-induced fluorescence has also been used for determining the density of NH and NH 2 produced by NH 3 decomposition on a heated tungsten filament. 22 For depositing systems, few studies of the NH 3 plasma chemistry using mass spectrometry have been reported, for example, for the ammonia-silane chemistry 23,24 and recently also for the ammonia-acetylene chemistry. 25 In both pure NH 3 plasmas and depositing plasmas, the chemistry is very complex and much remains unknown about the NH 3 dissociation and its products.…”
Section: Introductionmentioning
confidence: 99%